2020
DOI: 10.1053/j.gastro.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Between Distinct Cancer Driver Genes Underlies Intertumor Heterogeneity in Hepatocellular Carcinoma

Abstract: See Covering the Cover synopsis on page 1997. BACKGROUND AND AIMS: The pattern of genetic alterations in cancer driver genes in patients with hepatocellular carcinoma (HCC) is highly diverse, which partially explains the low efficacy of available therapies. In spite of this, the existing mouse models only recapitulate a small portion of HCC intertumor heterogeneity, limiting the understanding of the disease and the nomination of personalized therapies. Here, we aimed at establishing a novel collection of HCC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 40 publications
5
71
0
Order By: Relevance
“…In generating HCC models (Basic Protocol 1), careful attention should be paid on the age, strain, and gender of the animals used, as these may influence the phenotype of liver tumors and associated immune landscape. We recommend using 6‐ to 8‐week‐old C57/BL6J mice to enable the comparison of different HCC genetic backgrounds to what has been previously reported in the literature (Molina‐Sánchez et al., 2020; Wang et al., 2019), and working in sterile conditions during the preparation of the plasmid mix in endotoxin‐free solutions, and the subsequent HDTVi, using an IVC flow.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…In generating HCC models (Basic Protocol 1), careful attention should be paid on the age, strain, and gender of the animals used, as these may influence the phenotype of liver tumors and associated immune landscape. We recommend using 6‐ to 8‐week‐old C57/BL6J mice to enable the comparison of different HCC genetic backgrounds to what has been previously reported in the literature (Molina‐Sánchez et al., 2020; Wang et al., 2019), and working in sterile conditions during the preparation of the plasmid mix in endotoxin‐free solutions, and the subsequent HDTVi, using an IVC flow.…”
Section: Commentarymentioning
confidence: 99%
“…This protocol contains a brief description of the HDTVi procedure for generating HCC mouse models (Zhang et al, 1999). Examples of HCC mouse models obtained by this procedure and further applications of this technique have been reported in the literature (Molina-Sánchez et al, 2020;Wang et al, 2019). This approach allows the stable transduction of mouse hepatocytes to induce HCC by tail vein injection of a large volume of saline solution containing a combination of a Sleeping Beauty transposon for oncogene somatic integration, a vector encoding the Sleeping Beauty transposase, and a third vector expressing a single guide RNA (sgRNA) targeting the tumor-suppressor gene of interest, depending on the HCC oncogenic drivers of interest.…”
Section: Generation Of Hcc Mouse Models By Hydrodynamic Tail Vein Injectionmentioning
confidence: 99%
“…As an example, our laboratory has contributed to this field by functionally validating the role of β-catenin activation promoting immune escape and resistance to immunotherapy in HCC. Using genetic customizable mouse models of HCC [ 58 ], Ruiz de Galarreta et al demonstrated that activated β-catenin pathway promotes immune escape by defective recruitment of dendritic cells and consequent impaired T-cell activity [ 59 ]. This study suggested that specific genetic alterations found in HCC might be able to trigger different mechanisms to avoid anti-tumor immune responses.…”
Section: Inter-patient Heterogeneity In Hccmentioning
confidence: 99%
“…Despite the advances in the stratification of HCC patients, above summarized and supported by the implementation of high-throughput analysis [ 104 ], the integration of data obtained from human studies and preclinical models remains necessary to accelerate the identification of robust predictive biomarkers and classification of candidate patients to increase the efficiency of targeted and immune-based therapies. In that regard, our laboratory has recently used the hydrodynamic delivery of genetic elements to study how different genetic alterations cooperate with each other to contribute to different expression patterns, inter-tumor heterogeneity, and distinct patient responses [ 58 ].…”
Section: Inter-patient Heterogeneity In Hccmentioning
confidence: 99%
“…Specifically, we examined whether a circRNA construct can be delivered to the liver of mice via hydrodynamic tail vein injection. To enrich for cells that contain the circRNA construct, we used a hepatocellular carcinoma model in which tumorigenesis is driven by delivering a Sleeping Beauty transposon harboring a c-Myc cDNA 32 . We combined the spGFP transposon plasmid with a Sleeping Beauty transposase expression plasmid, the c-Myc transposon, and a plasmid encoding Cas9 and a sgRNA targeting p53 32 and performed hydrodynamic tail vein injections in wildtype C57BL/6 mice (Fig.…”
Section: In Vivo Delivery Of a Circrna Construct Using Transposonsmentioning
confidence: 99%